Religious Conflict among Pentecostal Churches in Uganda: A Struggle for Power and Supremacy - Isiko, Alexander Paul (Technium Social Sciences Journal, 2020)
Extensive research has been done on Pentecostal churches over the past years. Several studies have focused on their history and robust growth, some on their economic and developmental ethos, while others have focused on their theological stances, and growing political influence in society. Amidst these kinds of studies, is the need to address the overt challenge posed by religious conflict among Pentecostal churches. Whereas there is growing scholarly interest in religious conflict among Christian churches, this has been narrowed to intra-church conflict. However, studies on inter-church conflict, between separate Pentecostal churches, that are independent of each other, are rare. Yet inter-church feuds and conflicts among Pentecostal churches in Uganda occupy a significant part of public space and discourses. Through analysis of both print and electronic media reports and engagement with twenty key informant interviewees, this article sought to establish and analyse the nature, manifestations and root causes of inter-church conflict between Pentecostal churches in Uganda. The study established that Pentecostal pastors are not only the major protagonists of inter-church conflicts but also act as collective agents for the churches in conflict. The study further established that religious conflicts among Pentecostal churches are caused by different ideological inclinations, theological differences notwithstanding, but mainly by the desire to dominate the religious market and by power struggle dynamics within the religious leadership. This tension has a particular impact on society given pastors’ visibility, access to media and their public action in the Ugandan context.